The Effectiveness of Dialectical Behavior Therapy on Emotion Dysregulation and Social Cognition in Students With Self-Injurious Behaviors - Karmi, Abolfazl; Kiamarsi, Azar; Moghtader, Leila; Kazemi, Reza (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to determine the effectiveness of Dialectical Behavior Therapy on emotion dysregulation and social cognition in students with self-injurious behaviors. Methods and Materials: This study employed a quasi-experimental design using a pretest–posttest approach with a control group. The statistical population included all male upper secondary school students in Babol during the 2021–2022 academic year. The sample consisted of 30 students selected through convenience sampling and randomly assigned, using a lottery method, to an experimental group (n = 15) and a control group (n = 15). Participants completed the Deliberate Self-Harm Inventory (Gratz, 2001), the Difficulties in Emotion Regulation Scale (Gratz & Roemer, 2004), and the Social Cognition Questionnaire (Nejati et al., 2018) before and after the intervention. Dialectical Behavior Therapy was administered to the experimental group in twelve 90-minute sessions, twice weekly, while the control group received no intervention during this period. Data were analyzed using descriptive statistics (mean and standard deviation) and analysis of covariance (ANCOVA) with SPSS software, version 24. Findings: The results indicated that Dialectical Behavior Therapy had a significant effect on reducing emotion dysregulation and improving social cognition in students with self-injurious behaviors (P < 0.01). The mean ± standard deviation of emotion dysregulation decreased from 78.87 ± 7.12 at the pretest stage to 62.15 ± 6.04 at the posttest stage. Additionally, the mean ± standard deviation of social cognition increased from 56.55 ± 5.74 at the pretest stage to 67.82 ± 6.12 at the posttest stage. Conclusion: Based on the findings, Dialectical Behavior Therapy was effective in reducing emotion dysregulation and enhancing social cognition among students with self-injurious behaviors. Therefore, Dialectical Behavior Therapy can be recommended as an appropriate intervention for reducing problems in students who engage in self-injury.